Sosialisasi pembuatan alat komposter sederhana sebagai upaya pengelolaan sampah organik berkelanjutan di Universitas Sulawesi Barat: Promoting simple composters as a strategy for sustainable organic waste management at Universitas Sulawesi Barat - Andi Mawaddah Zakiyah; Muhammad Nasir Badu; Widyanti Utami A.; Nur Fitriani Maskur; Weny Anggraini Adhisty; Nur Aulia; Muh Fahrul Ar-Rahman; Hertika Anggraini (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2026)
The problem of organic waste remains a challenge on the campus of Universitas Sulawesi Barat, primarily because of the increasing activity of campus residents and the suboptimal awareness of sorting and managing organic waste. This community service activity aimed to improve the knowledge and skills of campus residents in making and using a simple composter to support sustainable organic waste management. The activity methods included socialization, demonstrations, direct practice, and evaluation. The participants in the activity included students, lecturers, and elements of campus leadership/staff. The material provided covered the importance of organic waste management, the potential for utilizing waste into compost and liquid organic fertilizer (LOF), and the stages of making a simple composter. The results of the activity showed that participants were actively involved in discussions and practices and were able to understand the basic stages of making a simple composter. After the activity was conducted, several academic communities at Universitas Sulawesi Barat began using simple composters, including the Faculty of Health Sciences, the Integrated Laboratory UPA, the Forestry Laboratory, and direct use practices at the homes of several lecturers. Although the activity has not yet reached the implementation of organic waste processing on a large scale, the existence of the simple composter has the potential to support the reduction of organic waste volume and encourage environmentally friendly behavior on campus.